Women's empowerment and its effect on their reproductive behaviour: a statistical analysis (Bangladesh Journal of Scientific Research, 2011)
Key words: Women's empowerment; reproductive behaviour; mobility; decision making autonomyBangladesh J. Sci. Res. 23(2): 169-180, 2010 (December)